The Effect of Nutrition Education on Knowledge about Anemia Prevention Using Flipchart Media among Middle School Students at the Istiqomah Samarinda Islamic Boarding School - Siti Khafifa; Lamri; Astri Ayu Novaria; Edi Sukamto (PT FORMOSA CENDEKIA GLOBAL, 2023)
Anemia is a condition where the number of red blood cells or hemoglobin levels in red blood cells is below the level that is considered normal. Knowledge can be increased through nutrition education and can be assisted by the media. The aim of this research is to determine the effect of nutrition education on knowledge about anemia prevention using flipchart media among junior high school students at the Istiqomah Islamic boarding school in Samarinda. Pre-experimental research design with One Group Pretest-Posttest design with 55 respondents using purposive sampling technique. Data analysis used the Wilcoxon test with a p-value of 0.001 which shows that there is a difference in the level of female students' knowledge before and after being given education using flipchart media on female students' knowledge at the Istiqomah Samarinda Islamic Boarding School, so that there is an influence of nutrition education using flipchart media on female students' knowledge about preventing anemia.